2018
DOI: 10.3390/quat1020014
|View full text |Cite
|
Sign up to set email alerts
|

Specifying the External Impact on Fluvial Lowland Evolution: The Last Glacial Tisza (Tisa) Catchment in Hungary and Serbia

Abstract: External impact on the development of fluvial systems is generally exerted by changes in sea level, climate and tectonic movements. In this study, it is shown that a regional to local differentiation of fluvial response may be caused by semi-direct effects of climate change and tectonic movement; for example, vegetation cover, frozen soil, snow cover and longitudinal gradient. Such semi-direct effects may be responsible for specific fluvial activity resulting in specific drainage patterns, sedimentation series… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 67 publications
(138 reference statements)
0
22
0
Order By: Relevance
“…The authors interpreted these similarities as an indicator for the importance of the Danube alluvium (DA) as the main sediment supplier and dust source in the LDB, corresponding to the MR mode of loess genesis (Li et al, 2020). However, the geochemical composition of the alluvial sediment changes laterally, as major tributaries in the MDB contribute to the sediment load of the Danube (Nenadić et al, 2016;Vandenberghe et al, 2018;Mitrinović et al, 2020). The influence of other local to sub-regional source areas for the loess of the Middle Danube Basin is evident in the range in the geochemical data of the reference sections from the MDB.…”
Section: The Danube Alluvium (Da) Sedimentary Pathwaymentioning
confidence: 99%
“…The authors interpreted these similarities as an indicator for the importance of the Danube alluvium (DA) as the main sediment supplier and dust source in the LDB, corresponding to the MR mode of loess genesis (Li et al, 2020). However, the geochemical composition of the alluvial sediment changes laterally, as major tributaries in the MDB contribute to the sediment load of the Danube (Nenadić et al, 2016;Vandenberghe et al, 2018;Mitrinović et al, 2020). The influence of other local to sub-regional source areas for the loess of the Middle Danube Basin is evident in the range in the geochemical data of the reference sections from the MDB.…”
Section: The Danube Alluvium (Da) Sedimentary Pathwaymentioning
confidence: 99%
“…However, even then large variability between aliquots and shine down curve shapes as well as poor recycling ratios were observed. In a later study, this complex behavior was not encountered, but overestimated dose recovery ratios led the authors to caution the quartz OSL results (Vandenberghe et al, 2018). The potassium feldspar samples, however, showed excellent luminescence characteristics.…”
Section: Discussion Geochronologymentioning
confidence: 96%
“…This shows potential for other studies on coarse-grained feldspars in the Carpathian Basin, as was already suggested for the deposits of the paleo Tisza River (cf. Popov et al, 2012;Vandenberghe et al, 2018). Nevertheless, it should be noted that the dated grain size fraction does not reflect the dominant sedimentological grain size (cf.…”
Section: Discussion Geochronologymentioning
confidence: 99%
See 1 more Smart Citation
“…Slano Kopovo is located at the northern part of the Vojvodina region, between regional roads Novi Bečej-Novo Miloševo-Kikinda and Novi Bečej-Bašaid (Figure 6. The saline soils here have been preserved in paleomeander on a terrace of Tisa River [27,28]. the summer dry season, when the shallow surface water evaporates and the basin becomes completely white with salts, contrasting well with the surrounding green to yellow agricultural fields.…”
Section: Study Areamentioning
confidence: 92%